A New Thermophilic Nitrilase from an Antarctic Hyperthermophilic Microorganism - Dennett-Rios, G; Blamey-Alegria, J (Frontiers Media S.A., 2016)
Several environmental samples from Antarctica were collected and enriched to search for microorganisms with nitrilase activity. A new thermostable nitrilase from a novel hyperthermophilic archaea Pyrococcus sp. M24D13 was purified and characterized. The activity of this enzyme increased as the temperatures rise from 70 up to 85°C. Its optimal activity occurred at 85°C and pH 7.5. This new enzyme shows a remarkable resistance to thermal inactivation retaining more than 50% of its activity even after 8 h of incubation at 85°C. In addition, this nitrilase is highly versatile demonstrating activity toward different substrates, such as benzonitrile (60 mM, aromatic nitrile) and butyronitrile (60 mM, aliphatic nitrile), with a specific activity of 3286.7 U mg-1 of protein and 4008.2 U mg-1 of protein, respectively. Moreover the enzyme NitM24D13 also presents cyanidase activity. The apparent Michaelis-Menten constant (Km) and Vmáx of this Nitrilase for benzonitrile were 0.3 mM and 333.3 μM min-1, respectively, and the specificity constant (kcat/Km) for benzonitrile was 2.05 × 105 s-1 M-1. © 2016 Dennett and Blamey.